Kemampuan Bacillus subtilis dalam mendegradasi limbah plastik polystyrene ditinjau dari perubahan berat kering dan spektrum Fourier Transform Infra-Red (FTIR) - Putri Darmansyah, Alifia; Purnamasari, Risa; Wazna Auvaria, Shinfi (Biotropic : The Journal of Tropical Biology, 2025)
Polystyrene is a type of plastic that is difficult to decompose naturally and  one of the main causes of environmental problems, especially in Indonesia, styrofoam waste in 2023 reached more than 32 million tons per year. This study uses quantitative descriptive and experimental methods to determine the ability of Bacillus subtilis bacteria to decompose polystyrene waste. The quantitative descriptive method was carried out by measuring the decrease in dry weight of polystyrene, while the experimental method was carried out by incubating 1x1 cm and 2x2 cm polystyrene samples with B. subtilis in Bushnell Haas media at 37°C for 40 days, with observations performed every 10 days. In addition, chemical changes in polystyrene were observed using Fourier Transform Infrared (FTIR) to see changes in functional groups. The results showed that the 1×1 cm sample experienced a weight loss of up to 20.65% after 40 days, while the 2×2 cm sample only decreased by 8.70%. FTIR analysis showed changes in absorption intensity and the appearance of carbonyl (C=O) and hydroxyl (O–H) groups, indicating the occurrence of oxidation and polymer chain cleavage. In conclusion, Bacillus subtilis was able to degrade polystyrene gradually, with effectiveness influenced by the size of the sample surface and the length of incubation time.